Museo a todo pedal: Calle 26 - Delgado, Catalina (2015)
This paper reviews the urban project “MUSEO A TODO PEDAL: CALLE 26” held to promote awareness and critical appropriation of the sculptural heritage of Avenida El Dorado in Bogota, Colombia. The urban project began in October 2014 with a series of activities including the official launch of the Guide on Monuments and Sites and the organization of a watching cycling road race. RevistArquis is honored to publish this project in dialogue with the essay by the same author published in Vol. 1 (2015) Number 07 “Usos Cotidianos y Populares de la Bicicleta en Bogotá”.